Correlation between reflux burden, peristaltic function, and mucosal integrity in GERD patients. Issue 3 (31st October 2019) - Ribolsi, Mentore; Gyawali, Chandra Prakash; Savarino, Edoardo; Rogers, Benjamin; Rengarajan, Arvind; Della Coletta, Marco; Ghisa, Matteo; Cicala, Michele
Abstract: Background: Mean nocturnal baseline impedance (MNBI) augments the diagnostic yield of multichannel intraluminal impedance‐pH (MII‐pH) monitoring. While acid exposure time (AET) correlates with MNBI, it remains unclear whether esophageal motility affects MNBI values. The present study was aimed at evaluating the respective roles of esophageal motor function and AET on MNBI. Methods: High‐resolution manometry (HRM) studies and ambulatory 24‐hour MII‐pH monitoring tracings were retrospectively analyzed from consecutive endoscopy‐negative GERD patients with typical symptoms responsive to previous acid‐suppressive therapy from three tertiary care centers. Univariate and multivariate analyses were performed to determine predictors of pathologic MNBI values at 3 cm and 5 cm above the lower esophageal sphincter (LES). Key Results: Patients with pathological AET displayed lower MNBI values at 3 cm and 5 cm ( P < .01) compared to patients with non‐pathological AET. Similarly, significantly lower MNBI values were also noted at both sites with type 3 EGJ compared to type 1 EGJ ( P ≤ .02 for each comparison), and with absent contractility compared to normal peristalsis ( P ≤ .02 for each comparison). On multivariate analysis, the presence of type 2 or 3 EGJ and absent contractility were associated with a significantly higher probability of pathological MNBI values at 3 cm and 5 cm above the LES. Conclusions and Inferences: Disruption of the EGJ and absent contractility on HRM are both associated with lower MNBI values. HRM findings complement reflux testing using MII‐pH monitoring. Abstract : The present study was aimed at evaluating the respective roles of esophageal motor function and AET on MNBI. High‐resolution manometry (HRM) studies and ambulatory 24‐hour Mil‐pH monitoring tracings were retrospectively analyzed from consecutive endoscopy‐negative GERD patients with typical symptoms responsive to previous acid suppressive therapy from three tertiary care centers. The present study demonstrates the adjunctive value of HRM in assessing for reflux evidence and confirms the value of MNBI in the evaluation of endoscopy‐negative patients. The HRM study performed to localize the LES for proper placement of Mil‐pH catheters therefore can be used to assess for the presence of hiatal hernia and major motility disorders that may influence the interpretation of baseline impedance.